Carbamoyl derivatives of a pyridine-based tetraamine - Heinemann, Frank Wilhelm; et al. (Zeitschrift für Naturforschung Section B-A Journal of Chemical Sciences, 2007)
The reaction of four equivalents of phenyl or tert-butyl isocyanate with the pyridine-derived tetraamine 2,6-C5H3N[CMe(CH2NH2)(2)](2) in toluene gives high yields of the quadruply ureido substituted products 2,6-C5H3N[CMe(CH2R)(2)](2) [R = -NH(CO)NHPh and -NH(CO)(NHBu)-Bu-t]. Full spectroscopic data for both compounds are given. A single crystal X-ray structure determination of the phenyl derivative reveals an intricate network of both intra- and intermolecular hydrogen bonds involving the C=O and both NH functionalities in all ureido groups.
Keywords: tetrapodal pentadentate ligand; urea; chelates; hydrogen bonding